A sorghum gigantea mutant attenuates florigen gene expression and delays flowering time. (13th November 2020) - Abdul‐Awal, S. M.; Chen, Junping; Xin, Zhanguo; Harmon, Frank G.
Abstract: GIGANTEA ( GI ) is a conserved plant‐specific gene that modulates a range of environmental responses in multiple plant species, including playing a key role in photoperiodic regulation of flowering time. The C4 grass Sorghum bicolor is an important grain and subsistence crop, animal forage, and cellulosic biofuel feedstock that is tolerant of abiotic stresses and marginal soils. To understand sorghum flowering time regulatory networks, we characterized the sbgi‐ems1 nonsense mutant allele of the sorghum GIGANTEA ( SbGI ) gene from a sequenced M4 EMS‐mutagenized BTx623 population. sbgi‐ems1 plants flowered later than wild type siblings under both long‐day or short‐day photoperiods. Delayed flowering in sbgi‐ems1 plants accompanied an increase in node number, indicating an extended vegetative growth phase prior to flowering. sbgi‐ems1 plants had reduced expression of floral activator genes SbCO and SbEHD1 and downstream FT‐like florigen genes SbFT, SbCN8, and SbCN12 . Therefore, SbGI plays a role in regulating SbCO and SbEHD1 expression that serves to accelerate flowering. SbGI protein physically interacts with the sorghum FLAVIN‐BINDING, KELCH REPEAT, F‐BOX1‐like (SbFFL) protein, a conserved flowering‐associated blue light photoreceptor, and the SbGI‐SbFFL interaction is stimulated by blue light. This work demonstrates that SbGI is an activator of sorghum flowering time upstream of florigen genes under short‐ and long‐day photoperiods, likely in association with the activity of the blue light photoreceptor SbFFL. Significance Statement: This study elucidates molecular details of flowering time networks for the adaptable C4 cereal crop Sorghum bicolor, including demonstration of a role for blue light sensing in sorghum GIGANTEA activity. This work validates the utility of a large publicly available sequenced EMS‐mutagenized sorghum population to determine gene function.